ChemInform Abstract: Ruthenium(II)‐Catalyzed C‐H Bond Activation and Functionalization. Issue 7 (22nd February 2013) - Arockiam, Percia Beatrice; Bruneau, Christian; Dixneuf, Pierre H.
Abstract Review: 259 refs.